ANALISIS FAKTOR YANG MEMPENGARUHI EKSPOR NONMIGAS DI INDONESIA - Kurnia Martikasari (Universitas Sanata Dharma, 2022)
This research aims to analyze factors that affect non-oil and gas exports in Indonesia: Gross Domestic Product (GDP), exchange rates (kurs), inflation, and foreign direct investment (FDI) for the period 2000 - 2019. This research is an ex post facto, where research is to examine data that have occurred and then trace back through the data to find the factors that determine the causes of the events under study. Data in this research is secondary data obtained from the Central Statistics Agency (BPS) for the period 2000 - 2019. The data analysis technique that will be used is Multiple Linear Regression. The results show that Gross Domestic Product (GDP), exchange rates and foreign investment (PMA) have a positive effect on Indonesia’s non-oil and gas exports for the period 2000 - 2019. Keywords: Non-Oil and Gas Exports, Gross Domestic Product (GDP), Exchange Rates (kurs) and foreign direct investment (PMA)